Animal tales from the Caribbean - List, George, 1911-2008 (Special publications of the Folklore Institute, 2017)
These 21 animal tales from the Colombian Caribbean coast represent a sampling of the traditional stories told during all-night funerary wakes, a ritual shared in the semi-sacred space of the patio (backyard) of homes. Such wakes also include other aesthetic and expressive practices such as jokes, song games, board games, and prayer. Situated within their performance contexts, the stories represent a highly ritualized corpus of oral knowledge that, for centuries, has been preserved and cultivated by African-descendant populations in the Americas. Ethnomusicologist George List collected these tales throughout his decades-long fieldwork among the rural costeños in the mid-20th century and, with the help of a research team, transcribed and translated them into English before his death in 2008. In this volume, John Holmes McDowell and Juan Sebastián Rojas E. bring this previously unpublished manuscript to light, providing commentary on the transcriptions and translations, addtional cultural context through a new introduction, and a further typological and cultural analysis by Hasan M. El-Shamy. Supplementing the transcribed and translated texts are links to the original Spanish recordings of the stories, allowing readers to follow along and experience the traditional telling of the tales for themselves. -- from back cover.